RESPON PEMBERIAN MONOSADIUM GLUTAMATE (MSG) AJI NO MOTO TERHADAP PERTUMBUHAN BIBIT TANAMAN KELAPA SAWIT (Elaeisguineensis Jacq.) DI PEMBIBITAN PRE NURSERY - Walida, Hilwa (JURNAL AGROPLASMA, 2015)
The ingredients of MSG derived from nature, especially vegetable materials, cause the MSG solution decompose with other substances. Utilization of Monosodium Glutamate (MSG) as a stimulant of plant growth can be applied to various types of plants. The aim of this study was to know the effect of MSG on the growth of oil palm seed (Elaeis guineensis Jacq.) in pre nursery. This research was conducted with 8 treatments and 3 replications, in which P0: Control, P1: 5 gram / 200 ml, P2: 10 gram / 200 ml, P3: 15 gram / 200 ml, and P4: 20 gram / 200 ml, P5: 25 gram / 200 ml, P6: 30 gram / 200 ml, P7: 35 gram / 200 ml. Observations were done after 4 MST with 2 weekly measurements up to 14 MST. The best rate of the height, the length and the number of leaves of the oil palm plant were at the dosage of P6 (30 grams / 200 ml). Keywords: Elaeis guineensis Jacq.,Monosodium Glutamate (MSG), Prenursery